2015
DOI: 10.1038/ki.2014.362
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-converting enzyme is a plausible target gene for hypoxia-inducible factor

Abstract: Renal endothelin-converting enzyme (ECE)-1 is induced in experimental diabetes and following radiocontrast administration, conditions characterized by renal hypoxia, hypoxia-inducible factor (HIF) stabilization, and enhanced endothelin synthesis. Here we tested whether ECE-1 might be a HIF-target gene in vitro and in vivo. ECE-1 transcription and expression increased in cultured vascular endothelial and proximal tubular cell lines, subject to hypoxia, to mimosine or cobalt chloride. These interventions are kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…, Khamaisi et al . ). The long list of acknowledged HIF‐target genes includes hexokinase, phosphofructokinase, aldolase, enolase, glucose transporters, adrenomedullin, erythropoietin (EPO), haeme‐oxygenase‐1 (HO‐1), carbonic anhydrase‐9 (CAIX), vascular endothelial growth factors (VEGF), transforming growth factor (TGF), insulin‐like growth factor (IGF) and its binding proteins, transferrin, transferrin receptor and ceruloplasmin, nitric oxide synthases, endothelin and endothelin converting enzyme‐1 (ECE‐1), adrenergic receptors, and many others (Schödel et al .…”
Section: Hypoxia‐inducible Factors (Hifs)mentioning
confidence: 97%
See 1 more Smart Citation
“…, Khamaisi et al . ). The long list of acknowledged HIF‐target genes includes hexokinase, phosphofructokinase, aldolase, enolase, glucose transporters, adrenomedullin, erythropoietin (EPO), haeme‐oxygenase‐1 (HO‐1), carbonic anhydrase‐9 (CAIX), vascular endothelial growth factors (VEGF), transforming growth factor (TGF), insulin‐like growth factor (IGF) and its binding proteins, transferrin, transferrin receptor and ceruloplasmin, nitric oxide synthases, endothelin and endothelin converting enzyme‐1 (ECE‐1), adrenergic receptors, and many others (Schödel et al .…”
Section: Hypoxia‐inducible Factors (Hifs)mentioning
confidence: 97%
“…The HIFab heterodimers, either directly or through mediators such as miR-687, induce transient epigenetic changes in the DNA, with histone modification and chromosomal conformational changes, leading to transactivation of HIF-target genes . Over 2000 HREs were identified along the mouse genome and there are over 200 genes clearly controlled by HIF , Khamaisi et al 2015. The long list of acknowledged HIF-target genes includes hexokinase, phosphofructokinase, aldolase, enolase, glucose transporters, adrenomedullin, erythropoietin (EPO), haeme-oxygenase-1 (HO-1), carbonic anhydrase-9 (CAIX), vascular endothelial growth factors (VEGF), transforming growth factor (TGF), insulin-like growth factor (IGF) and its binding proteins, transferrin, transferrin receptor and ceruloplasmin, nitric oxide synthases, endothelin and endothelin converting enzyme-1 (ECE-1), adrenergic receptors, and many others , Khamaisi et al 2015.…”
Section: Hypoxia-inducible Factors (Hifs)mentioning
confidence: 99%
“…Recently, we found that hypoxia triggers the induction of ET‐converting enzyme (ECE)‐1, a key moderator in the generation of ET‐1, via the inhibition if HIF‐prolyl hydroxylases (PHD), with subsequent stabilization hypoxia‐inducible factors (HIF) . We further documented altered renal microcirculation, hypoxia and HIF upregulation following CsA administration .…”
Section: Introductionmentioning
confidence: 83%
“…COX-2 and PGIS are enzymes with opposing actions in inflammation (He et al, 2010;Camacho et al, 2011). Besides VEGF, iNOS, ECE-1 and COX-2 are other target genes of HIFs in hypoxia (Branco-Price et al, 2012;Khamaisi et al, 2015;Zhao et al, 2015). Whether activated macrophages affect these factors in hypoxia-stimulated HCMECs via peroxynitrite is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to COX-2, prostacyclin synthase (PGIS) antagonizes inflammation and has cytoprotective properties (He et al, 2010;Camacho et al, 2011). In addition to VEGF, HIFs also contribute to the trans-activation of iNOS, ECE-1 and COX-2, which leads to injury (Branco-Price et al, 2012;Khamaisi et al, 2015;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%